The Relationship between Ergonomic Position and Disability Level Due to Low Back Pain (LBP) among Ceramic Craftsmen in Dinoyo Ceramic Village, Malang - Deka Bagus Binarsa; Tutik Purwanti; Ma’ruf Ilham Hanafi; Annisa Nurul Arofah (Perhimpunan Dokter Kedokteran Komunitas dan Kesehatan Masyarakat Indonesia (PDK3MI), 2026)
Low Back Pain (LBP) is one of the main Musculoskeletal Disorders (MSDs) caused by work, especially in professions that involve non-ergonomic postures such as ceramic craftsmen. This study aims to examine the relationship between ergonomic position and the level of disability due to LBP in this population. This study used an analytical observational method with a cross-sectional design conducted on 19 ceramic craftsmen in Kampung Keramik Dinoyo, Malang. The sample was selected using purposive sampling with the criterion of more than 5 years of work experience. The independent variable (Ergonomic Position) was measured using the Rapid Entire Body Assessment (REBA) worksheet, and the dependent variable (LBP Disability) was measured using the Modified Oswestry Low Back Pain Disability Questionnaire (MODQ). The data were analyzed using Spearman's correlation test. It was found that 100% of respondents had ergonomic risks, with 15 people (78.9%) in the moderate risk category and 4 people (21.1%) in the high risk category. Most respondents (89.5%) experienced LBP disability, with 11 people (57.9%) experiencing moderate disability and 6 people (31.6%) experiencing severe disability. The results of the Spearman correlation test showed a positive and statistically significant correlation between the level of ergonomic risk and the level of LBP disability (correlation coefficient r = 0.468; p-value = 0.043). There is a significant relationship between poor ergonomic positioning and increased disability due to LBP among ceramic craftsmen. These findings indicate the urgent need for ergonomic interventions to improve work posture and reduce the risk of functional disability among workers.